Body surface area as a novel risk factor for chylothorax complicating video‐assisted thoracoscopic surgery lobectomy for non‐small cell lung cancer. Issue 12 (16th October 2018) - Li, Shuangjiang; Wang, Yan; Zhou, Kun; Cheng, Shan; Wu, Yanming; Che, Guowei
Abstract : Background: The study was conducted to demonstrate the predictive value of body surface area (BSA) for chylothorax complicating video‐assisted thoracoscopic surgery (VATS) lobectomy for non‐small cell lung cancer (NSCLC). Methods: Large‐scale retrospective analysis was conducted on the data of 1379 patients who underwent VATS lobectomy between January 2014 and October 2017 at our institution. Receiver operating characteristic analysis was conducted to determine a threshold BSA value for the prediction of chylothorax. This optimal BSA cutoff, other clinicopathological variables, and P < 0.15 were included into a multivariable logistic regression model to determine the risk factors for chylothorax. Results: Twenty‐six patients (1.9%) developed postoperative chylothorax. The mean BSA in patients with chylothorax was significantly higher than in patients without (1.84 ± 0.14 vs. 1.73 ± 0.16 m 2 ; P = 0.001). A BSA of 1.69 m 2 was identified as the threshold value with maximum joint sensitivity (96.2%) and specificity (43.8%). Patients with BSA > 1.69 m 2 had a significantly higher incidence of chylothorax (3.0% vs. 0.3%; P < 0.001) and a longer hospital stay (log rank P < 0.001) than patients with BSA ≤ 1.69 m 2 . Multivariable logistic regression analysis suggested that BSA > 1.69 m 2 (odds ratio 7.35, 95% confidence interval 1.54–35.71; P = 0.013) was predictive of postoperative chylothorax. Conclusions: BSA can serve as a novel categorical predictor for chylothorax complicating VATS lobectomy for NSCLC. It may be more helpful to incorporate a BSA cutoff into routine risk stratification tools for lung cancer surgery.